Perlindungan Hukum bagi Pekerja Gig Economy: Perspektif Hukum Perdata di Indonesia - Putra, Rengga Kusuma; Ramadhan, Adi Suryo; Imalia, Tri; Widhiati , Greget; Kapsah (Universitas Sains dan Teknologi Komputer, 2024)
The gig economy has emerged as a global phenomenon, reshaping traditional work patterns, including in Indonesia. While offering flexibility to workers, this work model poses significant challenges concerning legal protection, especially in work relationships mediated by digital platforms. Gig workers often find themselves in vulnerable positions due to insufficient regulations and an imbalance in bargaining power between them and digital platforms. This study aims to analyze the legal protection for gig economy workers in Indonesia from a civil law perspective, highlighting gaps in existing regulations and offering recommendations for reform. This research employs a qualitative approach with a descriptive-analytical method. Data were obtained through literature review, analysis of electronic work contracts, and comparisons with gig economy regulations in other countries, such as the European Union and the United States. The findings reveal that electronic work contracts used by digital platforms in Indonesia are often unfair and favor the platforms. Furthermore, Indonesia’s gig economy regulations do not provide adequate protection, unlike countries such as the European Union, which have established minimum standards for gig workers' protection. This imbalance adversely affects gig workers’ welfare, including financial insecurity and lack of access to social security. This study contributes to the development of a more inclusive and equitable regulatory framework for gig workers in Indonesia. The implications include the need for civil law reforms to govern gig economy work relationships and the use of technology as a tool to enhance legal oversight. This research also lays the groundwork for future studies exploring the implementation of gig economy regulations in the context of other developing countries.